SHARENTING, DIGITAL SAFETY, AND INTERCULTURAL EDUCATION: RETHINKING GLOBAL PEDAGOGY IN THE AGE OF ONLINE EXPOSURE - Agnieszka Szajner (PUPIL: International Journal of Teaching, Education and Learning, 2025)
In an era of global connectivity, digital platforms play an increasingly central role in education and family life. However, the widespread practice of sharenting, parents sharing children’s images and data online raises pressing concerns about digital safety, children’s privacy rights, and cultural attitudes toward public exposure. These issues become particularly complex in multicultural and transnational contexts, where norms around family, identity, and technology vary widely. This presentation explores the intersection of sharenting, digital literacy, and intercultural education. It draws on recent international research and projects, including EU-funded studies to demonstrate how educational institutions can foster critical awareness of online safety and personal data protection. Special attention is given to immigrant families and global classrooms, where cultural dissonances and unequal access to digital competence can exacerbate risks. By integrating intercultural competence training, media literacy, and inclusive digital pedagogy, educators can help students and parents navigate the ethical challenges of digital sharing in diverse communities. Case studies include digital safety modules in multicultural schools, and cross-border campaigns that empower parents to make informed, culturally sensitive decisions about children’s digital footprints.